Assessment of Anti-Diabetic Activity of Vinca Rosea Extract on Induced Diabetic Mice - Eman H. Altaee1 , Abdulkarim J. Karim1, Mohammed M. Dakheel2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Objective: Vinca rosea is a medicinal plant that has been investigated and applied as analternative treatment for disorders. This study aimed to investigate the anti-diabetic activity of ethanolicextract of Vinca rosea on induced diabetes in mice.Methods: Forty male albino mice were randomly divided into four groups, including control that wasadministered a standard physiologic saline and served as control, diabetic group, Streptozotocin & Vincarosea, and only Vinca rosea; each group contained ten mice.Results: No significant lesions were observed in pathological sections of the control; however, the lesions indiabetic group showed massive lesions in the islets of Langerhans and reduced dimensions of islets due to thedamage of beta-cells. Furthermore, the Pancreas in Streptozotocin & Vinca rosea demonstrated a moderatedvacuolation and Langerhans of islet cells. In contrast, the histopathological sections of the pancreas, whichtreated by ethanolic extracts of Vinca rosea, illustrated increasing number of beta-cells hypercellularity. Thevalues of blood glucose were increased in the diabetic group; however, the significant decreases (P<0.05)in blood glucose detected in treated by ethanolic extract as represented by increased Beta-cells. While, theblood glucose levels were tolerated in treated Streptozotocin & Vinca rosea; thus, these values were closelyfor the control results.Conclusion: The Vinca rosea extracts induced a significant impact on diabetic mice, and they can improveand protect pancreatic cells in diabetic mice. Therefore, ethanolic extracts of Vinca rosea could be beneficialfor the diabetes.